Envisioning creation of a healthy city: The need, existing challenges, and potential actions - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Muller Journal of Medical Sciences and Research, 2019)
In an attempt to improve the living standards, millions of individuals have migrated to cities and the current estimates reveal that 50% of the global population are living in cities. However, the life in a city poses a wide gamut of challenges and it is important to understand that health standards are not only determined by access to health system but also by supporting infrastructure and facilities. All these facts emphasize the need to create such kind of cities that can shield and promote health through the implementation of appropriate policies, structural reforms, and launch of health programs. The creation of a healthy city requires some key issues to be addressed, including mental illness, physical inactivity, consumption of unhealthy diet, pollution and environmental health hazards, road traffic injuries, and urban violence. In conclusion, the creation of a healthy city should be looked upon as an opportunity to not only improve the well-being of the general population but also will aid in the accomplishments of universal health coverage, national, and global goals for development.